2017
DOI: 10.1002/anie.201610727
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Spatial Arrangement of Emitter Molecules in Organic Light‐Emitting Diode Films

Abstract: The effect of varying the emitter concentration on the structural properties of an archetypal phosphorescent blend consisting of 4,4'-bis(N-carbazolyl)biphenyl and tris(2-phenylpyridyl)iridium(III) has been investigated using nonequilibrium molecular dynamics (MD) simulations that mimic the process of vacuum deposition. By comparison with reflectometry measurements,w es howt hat the simulations provideanaccurate model of the average density of such films. The emitter molecules were found not to be evenly distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 16 publications
4
57
0
Order By: Relevance
“…For this analysis, a molecule or cluster was considered isolated if the nearest complex had an Ir–Ir distance of greater than 1.4 nm. This distance means that there is insufficient space for a TCTA molecule to be placed between neighboring Ir(ppy) 3 molecules based on the diameter of Ir(ppy) 3 being ≈1 nm . In addition, a distance of 0.4 nm is compatible with hopping transport of charges and Dexter energy transfer between neighboring complexes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this analysis, a molecule or cluster was considered isolated if the nearest complex had an Ir–Ir distance of greater than 1.4 nm. This distance means that there is insufficient space for a TCTA molecule to be placed between neighboring Ir(ppy) 3 molecules based on the diameter of Ir(ppy) 3 being ≈1 nm . In addition, a distance of 0.4 nm is compatible with hopping transport of charges and Dexter energy transfer between neighboring complexes.…”
Section: Resultsmentioning
confidence: 99%
“…All simulations were performed using the GROMACS simulation package version 2018.3 with GPU acceleration . Molecules were randomly deposited onto a 34.1 nm by 33.4 nm graphene sheet using a deposition protocol similar to that previously reported by Tonnelé et al During the deposition process, two new molecules were inserted 2 nm from the top of the film every 10 ps with a random orientation and an initial velocity toward the surface to ensure they reached the growing film. The initial positions and orientations of the molecules above the surface were selected randomly such that the centers‐of‐mass were separated in the plane of the substrate by at least 10 nm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…High efficiency phosphorescent OLEDs generally have the emissive guest at low doping concentrations on the order of 6–10 wt% and it is generally assumed that the emissive guest is evenly distributed throughout the EML. However, recent modeling studies of the deposition process of such emissive layers have shown that this is not necessarily the case and from an experimental perspective, there is clear evidence that increasing the emissive dopant concentration above a certain level leads to a decrease in efficiency …”
Section: Introductionmentioning
confidence: 99%